Rocking out! - Stern, A. J. (Frankly, Frannie, 2012)
"When Frannie's local community center, The Ark, announces it is going out of business, Frannie and the community join together to create a fundraising concert. Frannie and her friends write letters to rockstar Aimee Chapman asking her to perform at the concert and she says yes! Frannie and her friends learn all about the perks of being a rockstar and, of course, Frannie decides rock star is perfect for a career. After all, a green room is actually an office for rock stars!"--